Interaction of irrigation water salinity and substrate on the production of yellow passion fruit seedlings - Oliveira, Fernanda Andrade de; Lopes, Maria Ângela Casimiro; Sá, Francisco Vanies da Silva; Nobre, Reginaldo Gomes; Moreira, Romulo Carantino Lucena; Silva, Luderlândio de Andrade; Paiva, Emanoela Pereira de (Comunicata Scientiae, 2015)
The aim of the present study was to evaluate the yield og yellow passion fruit seedling according to the interaction between substrate composition and salinity levels of irrigation water in an experiment carried out from November, 2013 to January 2014, in a protected environment (greenhouse) at the Center of Science and Agrifood Technology - CCTA, Federal University of Campina Grande - UFCG, located in the municipality of Pombal, PB, Brazil. A randomized complete block design in a 4x3 factorial consisted of four levels of irrigation water salinity ECw (0.3, 1.5, 2.5 and 3.5 dS m-1) and three different substrates [S = soil; EO = Soil + sheep manure (2:1); and SC = soil + commercial substrate (2:1)], with a total of 12 treatments with three replications and three useful plants per replication were used. The increase in salinity of irrigation water reduced the emergence, growth and dry matter accumulation of passion fruit seedlings, being the total dry matter the variable that was most affected by salinity. The substrate containing soil + sheep manure in the ratio of 2:1 promoted the highest initial growth and dry matter accumulation of yellow passion fruit seedlings, using a maximun level of 1.5 dS m-1 of saline irrigation were used.